Application of dynamic systems modeling approach to rank optimal urban waste management strategies using SWOT method - Hamid Shahbandarzadeh; Mohammad Hossein Kabgani (تصمیم گیری و تحقیق در عملیات)
Purpose: In a city, there are different sectors in operation, and each sector also plays a role in the production of municipal waste, which draws attention to waste management methods. The present study explains a model to identify the factors affecting waste production in Bushehr.Methodology: The main dimensions of the model are taken from the review of the theoretical literature. A dynamic systems approach has also been used to identify urban waste management strategies. First, we identified and modelled the factors affecting municipal waste production with dynamic systems. The reasons for using the dynamic systems approach for this research can also be enumerated as follows: 1) an appropriate approach in determining and predicting the effects of factors affecting waste production, 2) helping to understand the relationships between variables and examining the behaviour and structure of systems, incredibly complex systems (creating a conceptual model), 3) a flexible approach with the ability to analyze quantitatively and qualitatively, 4) the ability to review the system in the future under different scenarios and policies of decision makers and 5) dynamic system models are considered as simulation models; therefore, they have the advantages of using the simulation method over the analysis methods. In the next step, the organization's internal and external factors in urban waste management were performed by referring to the SWOT analysis method, urban waste management strategies in Bushehr.Findings:  The results of the SWOT method showed that the vulnerability threshold of urban waste management in Bushehr is very high, and it is necessary to provide appropriate policies to address weaknesses and threats using strengths and opportunities. In the next step, Mikhailov's nonlinear method was used to rank the four strategies. This approach shows that among SO strategies, increasing awareness and changing citizens' attitudes towards proper waste management is in the first place. Among ST strategies, culturing for recyclable containers weighing 0.51 is in the first place. Employing knowledgeable people for proper waste segregation and disposal among WT strategies, with a weight of 0.57, was ranked first, and finally, the strategy of encouraging the private sector to invest, with a weight equivalent to 0.43 among WO strategies, Ranked first. Pollution from poor waste management in urban areas imposes irreversible health and aesthetic consequences on society. Among the consequences of poor waste management will be a variety of diseases. Environmental issues are also at the top of all human problems.Originality/Value:  In this research, an attempt has been made to examine innovation from three aspects: theoretical, technical and practical gaps, which can be mentioned as the strengths of the current research compared to other research. From a theoretical point of view, it has been tried to conduct a relatively comprehensive study of factors affecting urban waste management to formulate strategies. Also, from the technical point of view, the current research is innovative by focusing on combining fuzzy logic with the dynamic systems modelling approach and the Delphi method. Finally, it has been tried to reduce the practical vacuum of previous research in this field by formulating optimal strategies.